Differences between Modern Languages Students from Fourth Semester of Day and Night (2016)
This research aims to find out the differences between Modern Languages students from fourth semester of day and night at the University of Quindío related to their English proficiency level. It was carried out in two fourth semester groups, one from the day and one from the night. This investigation consists of an ethnographic research, a qualitative type of study. The data were collected through observations, interviews, questionnaires and the Michigan results. The findings revealed that students from the night do not have as much time as students from the day, therefore their performance does not equal the performance of the students from the day.